Chupacabra - Smith, Roland 1951- (New York : Scholastic Press, 2013)
Searching faraway world regions for Grace, who has been kidnapped by a ruthless grandfather who has also stolen two dinosaur hatchlings, Marty and his cryptozoologist uncle, Travis Wolfe, are distracted by a sighting of an elusive blood-drinking cryptid.
Sequel to: Tentacles.
Keywords: Chupacabras -- Juvenile fiction; Missing persons -- Juvenile fiction; Chupacabras -- Fiction; Missing persons -- Fiction; Adventure and adventurers -- Fiction